Análisis de las características físico-químicas y biológicas del suelo tras la incorporación de residuos agrícolas de cosecha en Almería-España. - Robledo Sandoval, Elisa Lizbeth (2023)
After the intensification of the production model in the greenhouse based on the application of high doses of mineral fertilizers and low or null contributions of organic matter, it has meant a deterioration in the quality of the soil derived from the leaching of nitrates. And if the difficulty of processing large amounts of organic waste is added to this, the need arises to move towards an alternative model that improves sustainability by improving soil quality, reducing dependence on external inputs and optimization of the use of resources. The present investigation analyzes the physical-chemical characteristics of the soil with the use of conventional management and management with fresh crop residues and horticultural crop residue compost (MCFrRH). And the state of organic matter through random sampling every thirty days in the crops implemented.The application of the MCFrRH package reduces soil compaction, due to the structure helping the stability of aggregates, by incorporating organic matter directly into the soil through organic amendments, significant changes in soil properties are observed. Together it reduces the need for inorganic fertilizers, however, it increases the risk of salinization by increasing the concentration of chlorides, nitrates and sulfates. For this reason, it is of great importance to increase organic practices, tillage or crop rotation.